Biomechanical effect of posterior ligament repair in lamina repair surgery. Issue 7 (19th May 2023) - Jin, Kaixiang; Zhu, Yuanjun; Li, Nan; Li, Yinghui; Yao, Yan; Mo, Zhongjun; Fan, Yubo
Abstract: Cervical laminectomy has usually been applied in treating cervical spinal cord tumour. However, spinal instability after laminectomy was observed with high occurrence rate, due to excising of posterior structures. This study was to investigate the biomechanical performances of ligament repair on the cervical stability in lamina repair surgery. A finite element of cervical spine model (C2-C7) was developed, and lamina repair surgery with and without ligament repair was simulated at C3-C6 segments. All models were loaded with pure moment of 1.5 Nm to produce flexion, extension, lateral blending and axial torsion. Compared to intact model, the range of motion (ROM) at C2-C3, C6-C7 increased by 12.8%-113.6% in lamina repair model (LRM), while the change of ROM in other segments was less than 9.2%. The change of ROM in all segments in the lamina and ligament repair model (LLRM) was less than 7.2%. The maximal intradiscal pressure (IDP) in adjacent segment (C2-C3 and C6-C7) increased by 73.7%, and the maximal stresses in capsular ligament increased by 168.6% in LRM model. By the other hand, the change of facet joint contact stress, IDP and stresses in capsular ligament in LLRM model were less than 11.5%. The differences of stresses on bone-screw interface and screw-plate system in C4, C5 between LRM and LLRM were less than 5.9 MPa (2.7%), but this value in C3 and C6 were up to 105.7 MPa (41.8%). Laminectomy without reconstruction of posterior ligament resulted larger mobility in the adjacent segments, which might induce spinal instability as postoperative complications. Repairing or preserving the posterior ligament in the lamina repair is benefit to spinal integrity and stability.